Band gap and Morphology Engineering of Hematite Nanoflakes from an Ex Situ Sn Doping for Enhanced Photoelectrochemical Water Splitting - Ahn, Hyo-Jin; Kment, Stepan; Naldoni, Alberto; Zboril, Radek; Schmuki, Patrik (ACS Omega, 2022)
In this article, we report a simple ex situ Sn-doping method on hematite nanoflakes (coded as MSnO2-H) that can protect the nanoflake (NF) morphology against the 800 degrees C high-temperature annealing process and activate the photoresponse of hematite until 800 nm wavelength excitation. MSnO2-H has been fabricated by dropping SnCl4 ethanol solution on hematite nanoflakes homogeneously grown over the conductive FTO glass substrate and annealed at 500 degrees C to synthesize the SnO2 nanoparticles on hematite NFs. The Sn-treated samples were then placed in a furnace again, and the sintering process was conducted at 800 degrees C for 15 min. During this step, structure deformation of hematite occurs normally due to the grain boundary motion and oriented attachment. However, in the case of MSnO2-H, the outer SnO2 nanoparticles efficiently prevented a shape deformation and maintained the nanoflake shape owing to the encapsulation of hematite NFs. Furthermore, the interface of hematite/SnO2 nanoparticles became the spots for a heavy Sn ion doping. We demonstrated the generation of the newly localized states, resulting in an extension of the photoresponse of hematite until 800 nm wavelength light irradiation. Furthermore, we demonstrated that SnO2 nanoparticles can effectively act as a passivation layer, which can reduce the onset potential of hematite for water splitting redox reactions. The optimized MSnO2-H nanostructures showed a 2.84 times higher photocurrent density and 300 mV reduced onset potential compared with a pristine hematite nanoflake photoanode.
CRIS-Team WoS Importer:2022-10-14